Effect of creep fracture mode transition of P91 steel welded joints on long-term creep fracture life - Denghui Wang; Fei Gao; Fulai Yang; Kai Yan; Zheng Zhang (Journal of Materials Research and Technology)
The formation mechanism of the two fracture behaviors and their effects on the creep life of P91 steel welded joints during creep were investigated, and the morphology and microstructure of the two fractures were characterized by SEM and EBSD, and the results were as follows: the change of fracture modes was affected by the creep strain rate and cavity nucleation rate in the joint. When the applied stress is large, the creep strain rate of BM is higher, and brittle fracture occurs at BM; when the applied stress is low, the cavity nucleation rate of FGHAZ is higher, and brittle fracture occurs at FGHAZ, known as type IV cracking. The occurrence of type IV cracking will reduce the accuracy of creep life prediction methods, and life prediction considering fracture mode can effectively improve the prediction accuracy.